Integrating media-and-material development tasks into anextensive reading class - Muniroh, Siti (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This article describes the integration of media-and-material development tasks in an Extensive Reading: Folk & Fairy Tales course. Fifty-eight students were instructed to write reflections on their experiences in performing reading and media-and-material development tasks. The results reveal that the practical application of teaching reading using materials for young learners was the most important aspect learned from the class. Moreover, most students reported that their creativity in media and material development, storytelling skills, and summarizing skills were enhanced through the tasks. The reading and media-and-material development tasks worked well for most students; nevertheless, some students viewed the caterpillar-making task as excessive. Meanwhile, the issues raised by students were mostly related to scoring standards, actions against plagiarism, and dissatisfaction with the caterpillar task. Thus, a clear description of assessment criteria and the omission of the caterpillar task are suggested for future practice.